FA’ALIYAH ISTIKHDAM AL-AL’AB AT-TA’LIMIYYAH EDUCAPLAY FI TAHSIN MAHARAT QAWAID AL-LUGHOH AL-ARABIYYAH LADAY THULLAB MADRASAH AL-MUTAWASSITHOH - Zahrotun Nida; Abdul Mutholib (Universitas Islam Negeri Mataram, 2025)
The aim of this study is to determine the effectiveness of using Educaplay-based educational games in improving Arabic grammar skills of class VIII MTs NU Ma’rifatul Ulum. This research is a quantitative with the pre-experimental research design in the one group pretest-posttest. Data in this study were obtained through interviews and pretest-posttest tests. Data analysis techniques used in prosecing data are normality test, t-test and N-Gain test. The population in this research were all students of class VIII MTs Ma’rifatul Ulum, while the sample of the research is 24 students. The results of the study show that the use of Educaplay-based educational games significantly improves students' understanding of Arabic grammar learning. This indicated by an increase in the average pre-test and post-test score. The result of paired sample T-Test obtained significance value of < 0,05, wich means there is a significant difference between before and after treatment. While the result of the N-Gain test were obtained at 61,3440, indicating an effective. This research contributes to the development of interactive Arabic grammar learning methods. This study recommends the use of educational games to enhance the quality of Arabic language learning for students at various educational levels.